A new edible Clavulina species from Hunan Province, China - Liu, Xiang-Fen; Deng, Peng-Tao; Wang, Xiao-Yan; Zhang, Ping (Phytotaxa, 2024)
Clavulina ruchengensis, a new edible mushroom, is described from three specimens collected in Hunan Province, central China, based on morphological and molecular evidence. This species is characterized by its gray basidiomata, cristate branch tips, and long stipes. Phylogenetic analysis of a combined dataset of internal transcribed spacer (ITS) and nuclear ribosomal RNA large subunit (nrLSU) sequences, revealed that the specimens formed a monophyletic lineage within the Clavulina clade, supporting their identification as a new species of Clavulina. A full description, illustrations, and phylogenetic analysis results of the new species are provided. In addition, a key to known Clavulina species in China is also provided.